Communities of learning and cultures of thinking: the facilitator's role in the online professional development environment - Simoneau, Carol Lynne Brooks (Kansas State University, 2007)
Online professional development has the potential to be a dynamic tool to construct knowledge and enhance professional performance. Online collaboration tools have accelerated learning and have made online professional development convenient, dynamic, and flexible. Yet access to powerful learning resources has not always ensured that quality online professional development has taken place or that authentic, transformational learning has occurred. This study has shown that technology has presented challenges that have proved difficult for online professional development facilitators and participants. Consequently, the facilitator's role in professional development has been even more critical in the virtual environment and the facilitator has had to be even more intentional in their actions, decisions, and expectations. The purpose of the study was to research, develop, and validate an online professional development facilitator's handbook that would clarify and demonstrate the knowledge, attitudes, practices, and skills utilized by exemplary online professional development facilitators. This study has also ascertained practical instructional strategies that are effective in planning, implementing, and facilitating online professional development. As a result of this study, an online professional development handbook was developed according to Borg and Gall's (1989) Research and Development (R&D) cycle and methodology using three panels that consisted of expert and novice online professional development facilitators. Findings include: Learning, defined as the process of constructing personal understanding through interactions with others while collectively engaging in challenges that are novel and transferable to other situations and settings, is transformational and has a sustaining impact when skillfully facilitated in the online environment. Online learning communities organized around collaborative inquiry and collective problem solving become co-creators of knowledge in a risk-free, trusting environment. Participants (teachers) become self-determining learners focused on engaging in appropriate endeavors to increase their classroom content knowledge and management skills by identifying their own needs and creating a plan to raise academic achievement and improve their own practices. When educational systems invest in honest dialogue about student work, candidly assess student and teacher needs, make changes based on data and research, and value individual and group contributions, these organizations become cultures of thinkers and communities of learners.
Keywords: online; facilitator; professional development; constructivist; adult learner; learning communities; Education, Administration (0514); Education, Curriculum and Instruction (0727); Education, Teacher Training (0530)